Old age poverty in developing countries : contributions and dependence in later life - Barrientos, Armando (2003)
Provides a perspective on old age poverty and notes that old age poverty is a significant issue in developing countries. Argues that understanding poverty in later life, and developing appropriate policy, requires acknowledging the contribution of older people to their households, communities, and the development process.